Creating web-based interactive public display applications with the PuReWidgets toolkit - Cardoso, Jorge C. S. (2012)
Interaction is repeatedly pointed out as a key enabling element towards more engaging and valuable public displays. Still, most digital public displays today do not support any interactive features. We believe that this is mainly due to the lack of e!cient and clear abstractions that developers can use to incorporate interactivity into their applications. In this demo we present PuReWidgets, a toolkit that developers can use in their public display applications to support the interaction process across multiple display systems, without considering the speciﬁcs of what interaction modality will be used on each particular display. PuReWidgets provides high-level widgets to application programmers, and allows users to interact via various interaction mechanisms, such as graphical user interfaces for mobile devices, QR codes, SMS, etc.